Effect of Feed Combination of Avocado (Persea americana M.) and Pumpkin Seed (Cucurbita moschata Duch.) on Villi Height and Goblet Cell Number of Goblet Fish (Osphronemus gourami Lac.) - Safrida Safrida; Muhibbuddin Muhibbuddin; Halimatussakdiah Halimatussakdiah (Jurnal Penelitian Pendidikan IPA, 2021)
In Indonesia, there are several types of freshwater fish that the community has cultivated. Besides having high nutritional value, Freshwater fish also have high economic value for trading, such as gourami. One of the obstacles in the cultivation of freshwater fish is the price of feed. This research is oriented towards alternative feeds to reduce production costs by utilizing avocado seeds and pumpkin seeds. This study aimed to determine the effect of feeding a combination of avocado seeds and pumpkin seeds on the histopathology of gourami. This study used a non-factorial completely randomized design (CRD) method with four treatments and six replications P0, P1, P2, and P3. P0 (Control feed/pellet), P1 (Feed 40 grams of avocado seeds + 40 grams of pumpkin seeds + 20 grams of mixed ingredients), P2 (Feed of 20 grams of avocado seeds + 60 grams of pumpkin seeds + 20 grams of mixed ingredients) and P3 ( Feed 60 grams of avocado seeds + 20 grams of pumpkin seeds + 20 grams of mixed ingredients). Data were analyzed using ANOVA and Advanced Test with a significant level of 5%. The results showed that the P2 treatment could increase the villi height and the number of Goblet cells in the intestines of gourami fish. It can be concluded that the combination of avocado seeds and pumpkin seeds has a significant effect on the histopathological picture of the digestive organs of gourami